Role of educational intervention with practical demonstration in improving inhaler technique - Bhushan, Bharat; Singh, Kulbir; Abraham, Jebin; Goyal, Deepak; Bhatnager, Arjun; Chungath, Jain Thomas; Bharti, Heena; Sharma, Karan (International Journal of Advances in Medicine, 2019)
Background: Chronic respiratory diseases are among the leading causes of morbidity and mortality worldwide with chronic obstructive pulmonary disease (COPD) and asthma being the most common. There is under-utilization of the basic tools of inhalation therapy technique(s) in their management. Implementation of a personalized educational and demonstrational intervention by the attending physician during regular follow-up visits of these patients will substantially improve the treatment outcome. Methods: This prospective interventional study was conducted on 239 diagnosed cases of asthma and COPD. Inhaler technique was assessed in accordance to standard checklist and errors were corrected by a practical demonstration. A follow-up assessment was conducted for the same after 2 weeks. Data thus collected was evaluated. Results: Out of 239 patients, 47.6% (n=114) reported for follow-up assessment. Average reporting time for follow-up assessment was 27.4 days. Amongst them, an improvement of at least one step was found in 86.8% (n= 99) and about 28% (n=32) patients performed all steps correctly. Average number of steps improved was 2.1. Conclusions: Majority of the patients showed an improvement in the inhaler technique during follow-up assessment after an educational intervention and practical demonstration. Near perfection was achieved by about more than quarter of the patients. Regular practical demonstration of the inhalation technique during subsequent follow-up sessions unequivocally improves results.